Nikah Bawah Tangan Dan Itsbat Nikah - Abd. Basit Misbachul Fitri (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
Underground marriage, also known as "pernikahan dibawah tangan" in Indonesian, refers to a marriage that is conducted secretly without the presence of anyone except the individuals getting married. This type of marriage is hidden from the public and is not officially recorded by authorized institutions. Underground marriages are considered valid according to religious principles (if the conditions and requirements are fulfilled), but they lack legal recognition from the state. The Indonesian Council of Ulama (Majelis Ulama Indonesia or MUI) issued a fatwa in 1980 stating that "underground marriage is valid if the conditions and requirements of marriage are fulfilled, but it is forbidden if there are harmful consequences. Marriages should be officially recorded by the relevant authorities as a preventive measure to reject negative impacts (madharat or harmful consequences). "Underground marriages have negative legal implications, particularly for the husband, wife, and their children, in terms of psychological, administrative, lineage, economic, and even religious aspects. The harmful consequences outweigh the benefits. This type of marriage can be resolved by applying for a marriage determination (itsbat nikah) in the Religious Court through a judicial process that meets the legal requirements. The purpose of itsbat nikah is to establish order in marriage within society and ensure the protection of the rights of those involved in the marriage.